Effect of ischemic preconditioning and postconditioning on exosome-rich fraction microrna levels, in relation with electrophysiological parameters and ventricular arrhythmia in experimental closed-chest reperfused myocardial infarction - Spannbauer, A. (MDPI AG, 2021)
10.3390/ijms20092140